A new approach to fault-line selection of small current neutral grounding system. Issue 3 (21st September 2018) - Chen, Yujie; Chen, Huiwei; Song, Baoye; Liu, Yanni; Liu, Peixue
ABSTRACT: In this paper, a new approach combining BP neural network with fuzzy Petri net (FPN) is developed to deal with the issue of fault-line selection of the small current neutral grounding system. First, the preliminaries of the FPN are briefly introduced. Then, the model of the fault-line selection is detailedly described to explain the new feature representation that fuses multiple fault features of the lines, including the wavelet energy, the active component and the fifth harmonic component. Finally, the simulation model of the fault-line selection is constructed, and the simulation experiments are carried out to verify the effectiveness of the new approach, which could be superior to the traditional fault-line selection approaches.